Dataset for OTDR-Integrated D-shaped Optical Fiber Sensor for Refractive Index Detection - Afiq Arif Aminuddin Jafry (20813003) (2025)
We demonstrated an Optical Time Domain Reflectometer-based refractive index (RI) sensor for RI detection. A bare fiber and a D-shaped fiber structure were utilized as a sensing probe. Both probes were connected to an OTDR via a single-mode fiber before the probe was immersed in a solution with different RIs. Results show a bare fiber owns a sensing sensitivity of 17.226 dB/RIU, while a D-shaped fiber has a sensitivity of 12.835 dB/RIU. The D-shaped fiber probe has a higher linearity of 0.9985 compared to 0.9341 for bare fiber, indicating the D-shaped fiber is more reliable for RI detection.